The Songs of the Sage : (4Q510, 4Q511) - Angel, Joseph L. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2022)
Since its discovery at Qumran in the 1950's, those wishing to study the Songs of the Sage (4Q510, 4Q511) had to approach a scattered grouping of fragments that gave little indication of the overall sequence, structure, and scope of the original composition. In the present volume, Joseph Angel remedies this situation by providing a new edition according to the sequence of the fragments determined by the material reconstruction of the more extensive manuscript, 4Q511. In addition to numerous enhanced readings and fresh English translations, the volume includes a general introduction, apparatus of variant readings, contextualizing commentary, catalog of photographic evidence, and key-word-in-context concordance. This work represents an unparalleled and comprehensive resource for anyone interested in the Songs of the Sage.